PENINGKATAN PENGETAHUAN DESAIN PRODUK KERAJINAN BERBAHAN ALUMUNIUM BAGI INDUSTRI KECIL UNTUK MENDUKUNG KETAHANAN EKONOMI - Dedet Hermawan Setiabudi; Abdul Haris Subarjo; Benedictus Mardwinata (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
This Community Service activity aims to make Karangtaruna "Taruna Bakti" Trayeman Pleret Bantul know about AutoCAD software, make product designs using AutoCAD software. The method used in training is through presentations, questions and answers, discussion and practice. The target audience in this community service activity are 15 members of Karangtaruna "Taruna Bakti" Trayeman, Pleret, Bantul. Based on the activities that have been carried out, the results obtained by Karangtaruna "Taruna Bakti" members can recognize and understand the use of AutoCAD software, through the practice activities of Karangtaruna "Taruna Bakti" members who can design aluminum-based products using AutoCAD software. It is hoped that after being able to use the AutoCad software they can design the product and make the product and then sell it, so they will be able to earn income and increase their economic reseliance. To analyze the condition of community service partners, the SWOT Analysis method uses strengths, weaknesses, opportunities and threats. With this SWOT analysis we can know internal-external factors and opportunities that can be optimized. One of the potential optimizations can be done by training human resources.